Teachers’ Reflections on the Use of Animation Media in Teaching Islamic Religious Education at SMP Rahmat Islamiyah Medan - Setiawan, Hasrian Rudi; Maysarah, Maysarah (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to explore teachers’ reflections on the use of animation media in teaching Islamic Religious Education at SMP Rahmat Islamiyah Medan. The research employed a qualitative approach with a phenomenological method, where data were collected through in-depth interviews, observations, and documentation. The findings reveal that the use of animation media has a positive impact on student engagement, understanding of religious concepts, and creates a more engaging learning atmosphere. Teachers also faced challenges related to technological readiness and limited resources. Nevertheless, they believe that animation media effectively helps convey Islamic teachings in a more visual, interactive, and contextual manner. The study recommends enhancing teacher training in digital media usage and developing animation content aligned with the Islamic Education curriculum.